Using Learners’ Diaries to Investigate the Influence of Students’ English Language Proficiency on Peer Assessment - Zhao, Huahui (Journal of Academic Writing, 2011)
Peer assessment has been used increasingly in English writing instruction in the past two decades. This has given rise to research on peer assessment in developing English learners’ writing proficiency. However, few studies have exclusively examined student variables in relation to peer assessment and, in particular, how students’ English language proficiency affects the use of peer assessment in English-medium writing classrooms. The case study research described in this article examined, through the employment of students’ learning diaries, how Chinese university English- learners’ language proficiency affected the use of peer assessment. Ten second-year English majors at a university in Southern China were asked to keep diaries of their experiences of being involved in peer assessment over sixteen weeks. The diary data showed that the students viewed their English language proficiency as a salient variable influencing the focus, the type, the appropriateness, and the impact of peer feedback on learners’ redrafts.